Bursaries reimagined: addressing digital inequity through a library-led, university-wide laptop bursary program - King, Martina; Whitson, Lindsey (My University, 2023)
The rapid switch to online learning in early 2020 exacerbated problems students were already having with obtaining and maintaining up-to-date devices and a reliable internet connection. MacEwan University Library began offering 4-month term laptop loans at the beginning of the pandemic, but it was clear this was not fully meeting student needs. In response to conversations with faculty and students, the library secured funds from the university’s Student Technology Fee to launch a laptop bursary pilot in Winter 2022, which in turn expanded to a university-wide bursary in Fall 2022. This article discusses why an in-kind laptop bursary was the right approach at the right time in this setting; how this initiative contributes to equity and accessibility; and finally, perceptions of the value of this work, its fit within the scope of the library, and how the unique position of the library as a stu-dent-focused service and academic unit positioned it well to successfully offer this bursary. Challenges and opportunities for improvement are also discussed.
Keywords: digital divide; equity; inclusion; laptop-provision; libraries; technology lending; user focus; user service